2005
DOI: 10.1039/b503216d
|View full text |Cite
|
Sign up to set email alerts
|

Study of mercury–selenium interaction in chicken liver by size exclusion chromatography inductively coupled plasma mass spectrometry

Abstract: In order to estimate metal distribution patterns in biomolecules of different sizes and their possible modification after long-term Hg and Se exposition, multi-elemental distribution of the cytosols of chicken livers were evaluated. For this purpose 72 chickens were fed under different controlled conditions. Chickens were exposed to Hg(II) and MeHg added to feed with or without selenium supplementation. Size-exclusion chromatography with ICP-MS detection was developed for multielemental (S, P, Cu, Zn, Se, Mn, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 40 publications
1
16
0
1
Order By: Relevance
“…One suggests that Se may enhance or enable detoxification processes by freeing methylmercury from its protein bonds, potentially making it available for demethylation [15]. The other hypothesis is that Se acts as a receptor for IoHg after it has been demethylated in the liver and binds with IoHg to form toxicologically inert Hg‐Se compounds [17,35–38]. Our results generally support the latter hypothesis that Se does not enhance demethylation but instead provides a binding site after MeHg has been converted to IoHg for the formation of nontoxic, nonlabile Hg‐Se compounds that are stored in the liver.…”
Section: Discussionsupporting
confidence: 71%
“…One suggests that Se may enhance or enable detoxification processes by freeing methylmercury from its protein bonds, potentially making it available for demethylation [15]. The other hypothesis is that Se acts as a receptor for IoHg after it has been demethylated in the liver and binds with IoHg to form toxicologically inert Hg‐Se compounds [17,35–38]. Our results generally support the latter hypothesis that Se does not enhance demethylation but instead provides a binding site after MeHg has been converted to IoHg for the formation of nontoxic, nonlabile Hg‐Se compounds that are stored in the liver.…”
Section: Discussionsupporting
confidence: 71%
“…Later, studies with human malignant melanoma cells demonstrated that arsenite-induced apoptosis is prevented by selenite [32]. A Human cells As-induced apoptosis is prevented by Se [32] A Mice As prevents carcinogenic effect of Se [30] A Rats As prevents carcinogenic effect of Se [31] A Rats As protects against the toxicity of Se (growth, mortality rate, pathological condition of the liver) [20,33,186] A Rats As induces mucosal glutathione synthesis, explaining its protective effect against Se [187] A Dogs As antagonizes Se-induced subnormal growth and restricted food intake [35] A Cattle As protects against Se toxicity [36] A Hogs As protects against Se toxicity [ Se prolongs the half-lives of Hg-exposed animals [190] A Rats Se changes the subcellular Hg distribution [191] S Oysters High levels of Se increase Hg toxicity [192] SeO 3 2− /MeHg + A Chickens Se changes the subcellular and pattern distribution of Hg [193] A Medaka fish Se protects against Hg-induced histopathological changes [151] SeO 2 /Hg 2+ A Chicks Se toxicity is decreased by Hg [194] SeO 4 2− /MeHg + A Mice Se protects against Hg-induced neurotoxicity [63] Protective effects of arsenic in rats [19,20,23,33,34], dogs [35], cattle [36], mice [37], hogs [38], steers [39], mallards [40] and poultry [41][42][43] have been observed/proposed. Several studies apparently suggest that the same interaction can occur in humans [44][45][46]…”
Section: Arsenic and Seleniummentioning
confidence: 99%
“…inductively coupled plasma mass spectrometry (ICP-MS), SEC can be used to fractionate free and macromolecule-bound metals [24-26]. A few studies have employed this technique to study the interactions between metals and macromolecules, particularly biological macromolecules such as proteins [27-31]. SEC-ICP-MS has not been used for direct speciation of dissolved free and DOM-bound As, although it was used to determine As distribution in soil humic acids [24].…”
Section: Introductionmentioning
confidence: 99%